Clinical profile and risk factors associated in patients of mucormycosis in COVID-19 pandemic: a study in a tertiary centre - Anas, M.; Choudhary, R. K.; Alam, Noman (International Journal of Research in Medical Sciences, 2021)
Background: The objective of this study was to determine the clinical profile and risk factors associated in patients of mucormycosis in COVID-19 pandemic. Methods: It was a prospective observational study conducted at a tertiary care centre in the month of May and June 2021. It involved all patients of mucormycosis mainly involving paranasal sinuses and orbit. The clinical profile and associated risk factors leading to mucormycosis were studied. Results: Thirty patients of mucormycosis mean age 56.62 years out of them 25 (83.33%) male and 5 (16.66%) female were studied. Twenty-four patients (80%) had COVID-19 infection, out of them 7 (29.2%) were active and 17 (70.8%) had recovered within 4 weeks. Five (16.6%) patients were suspected as they had symptoms of COVID-19 previously but never got tested. One patient had no history of COVID infection. All the patients were diabetic at the time of presentation, out of them 26 (86.6%) of patients were known diabetic and 4 (13.3%) became diabetic after COVID-19 infection. The ethmoids were the most common sinuses affected. Intra-orbital extension was seen in 13 (43.3%) of cases while intracranial extension was seen in 4 (13.3%) patients. Twenty-eight (93.3%) patients gave history of steroids intake. Antibiotics were taken by 76.6% patients while zinc supplement was used by 83.3% patients. Oxygen was used 10 (33.3%) patients, 80% of them using face mask or canula and 4 of them requiring mechanical ventilatory support. Conclusions: The risk factors associated with mucormycosis in COVID pandemic must be given serious consideration as there is sudden increase in the case and mortality is very high. Uncontrolled diabetes and over use of steroids in COVID management are two main aggravating factors, however other factors must also be studied thoroughly.